Pengaruh E-Wom Pada Media Sosial Tiktok Terhadap Brand Image Serta Dampaknya Pada Minat Beli - Erika Desi Lestari; Ce Gunawan (CV ODIS, 2021)
This study aims to examine the effect of Electronic Word of Mouth (EWOM) on TikTok social media on Brand Image and its impact on buying interest in Scarlett Whitening products in Sukabumi City. The type of data used in this research is quantitative data. This study uses descriptive analysis techniques and path analysis using the SPSS program. The population of this research is the people of the city of Sukabumi who use social media, TikTok. The location is in the city of Sukabumi, West Java. Based on the Slovin formula, the number of research samples to be used is 100 people. The results showed that the variable electronic word of mouth had a positive and significant effect on brand image and had an impact on consumer buying interest. Based on the information they get from consumer reviews via TikTok social media, the people of Sukabumi can find out the quality and benefits of the Scarlett whitening product.